Evaluation of Native Biocontrol Agents against Fusarium solani f.sp. melongenae Causing Wilt Disease of Brinjal in Kashmir - M.S. Khar*, A.G. Najar, Ali Anwar, Lubna Masoodi and (Journal of Phytology, 2011)
In the present study the native biocontrol agents (BCA) were isolated from rhizosphere viz. Gliocladium roseum from apple; Paecilomyces varioti, Trichothecium roseum and Aspergillus flavus from mulberry; Trichoderma viride (isolate-I&II) of mushroom and pea; Trichoderma harzianum (isolate-I &II) of pea and paddy while Pseudomonas fluorescens of rajmash and cultured on PDA/king’s B medium. All the native BCA’s were evaluated in vitro against Fusarium solani f.sp. melongenae causing wilt disease of brinjal. Except Gliocladium roseum and Trichothecium roseum all the fungal BCA’s were more effective than bacterial BCA ie. Pseudomonas fluorescens, whereas, Trichoderma harzianum isolate-I caused maximum inhibition(70.79%) followed by T. viride isolate-I(68.57%), T. harzianum isolate-II(63.80%), T.viride isolate-II(60.0%), Paecilomyces varioti(53.33%) and Aspergillus flavus(46.34%) but Trichothecium roseum and Gliocladium roseum were the least effective and resulted 18.09 and 27.61 per cent inhibition of wilt pathogen respectively. The bacterial bioagent, Pseudomonas fluorescens was slightly more effective (28.17%) against wilt pathogen. Similarly, in vitro agar plug test, T. viride(isolate-I&II), A.flavus, G.roseum and T.roseum were created inhibition zones but rest fungal BCA’s were advanced and occupied the entire plate within 10-20 days whereas P. flourescens did not show further advancement beyond the zone of contact.